Digitalization Strategy for Tailoring UMKM Branding in Mainan Village Banyuasin - Callistasari, Nidia Putri; Jannah, Raudatul; Aldi, Muhammad Rahmad; Alie, Juhaini; Munandar, Aris; Ghina, Aliah (Manunggal Halim Jaya, 2025)
This Community Service Program (KKN) was conducted in Mainan Village, Sembawa District, Banyuasin Regency, with a focus on branding digitalization strategies for local sewing MSMEs. The home-based sewing business targeted by the program is owned by Mrs. Sandiya, who previously lacked a business identity, such as a brand name, logo, banner, or attractive product packaging. The methods used included surveys and interviews, planning, implementation, and evaluation. The implementation stages included creating the business name